Psychological Well-Being pada Santri Ngrowot Di PP. Haji Ya’qub Lirboyo Kota Kediri - Muhammad Kurnia Mardhika; Beti Malia Rahma Hidayati (Universitas Islam Tribakti Lirboyo Kediri, 2019)
Islamic boarding schools do not only play a role in transferring religious knowledge, reconstructing character but also purifying the heart. This positive spirit needs to be explored by students through implementation to actualize themselves both physically and mentally. Students are also familiar with the practices and mindstreem traditions, including the traditions found in the Pondok Pesantren Haji Ya’qub (PPHY), which is named Ngrowot. Seeing the tradition of Ngrowot from the perspective of psychological well-being is very urgent because generally, people today assume that welll being is more to be a hedonic lifestyle. This study aims to examine the psychological well-being of Ngrowot implementation of the students at the Pondok Pesantren Haji Ya’qub (PPHY) which still exist although it is being a minority with demands and restrictions on eating the rice. Data obtained through interviews and observations then analyzed by using Islamic psychological theory and psychological well-being from Ryff. The results showed that there are four motives drive students in practicing Ngrowot: ; 1) ‘ulumiyyah, 2)‘amaliyyah, 3) dzuriyyah, and 4) maliyyah. Students who apply Ngrowot in PPHY have good psychological well-being with positive psychological function that is fulfilled. The implementation of Ngrowot shows the role of mental/ psychological processing in achieving life goals and finding psychological well-being which is a reflection of the religiosity and eudemonics welll-being concepts. So, Ngrowot can be a method of increasing psychological well-being based on cultural and Islamic-based